ANALYSIS OF THE NEED FOR THE DEVELOPMENT OF INDONESIAN LANGUAGE TEACHING MATERIALS INTEGRATED WITH CHARACTER STRENGTHENING - Kodrat Hi Karim; Risna Srinawati; Taufik Abdullah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the need for developing Indonesian language teaching materials integrated with character strengthening for grade 4 students at Publik Elementry School 38 Ternate. The study uses a Research and Development (R&D) model with the Haffin & Peck approach and a descriptive qualitative data type. Data collection techniques used include interviews and questionnaires distributed to students and teachers to explore perceptions and needs related to integrating character strengthening into Indonesian language learning. The results of the study show several main issues: the lack of integration of character in the existing teaching materials, as well as the limitations in using teaching materials based on local wisdom. The target of this research includes students and teachers, with the goal of identifying the need for more relevant teaching materials that support character strengthening. The research tasks include analyzing the existing teaching materials, evaluating character education, and mapping local wisdom that can be integrated into the learning process. The school and social environment also play a crucial role, with parental involvement, access to technology, and local wisdom being factors that support or hinder the development of teaching materials. Based on these findings, the study concludes that there is an urgent need to develop innovative Indonesian language teaching materials that are character-based and integrated with local wisdom, which can enhance the quality of learning at Publik Elementry School 38 Ternate.